Forgiven of Administrative Documents as A Official The Criminal Action Of Corruption at The Mataram Corruption Court - Fathur Rauzi; Firzhal Arzhi Jiwantara (LEGAL BRIEF, 2022)
The fundamental question from legal observers is why the offense of forgery contained in Article 416 of the Criminal Code (Book of the Criminal Law) is transformed into a Corruption Crime offense as contained in Article 9 of Law no. 31 of 1999 Jo. UU no. 20 of 2001 concerning the Eradication of Corruption Crimes. The approach method used in writing this journal is a normative juridical approach or commonly called normative legal research. This study also uses an empirical juridical approach, this is done to determine the validity of a norm in court decisions, especially in cases of applying article 9 in the decision at the Mataram Corruption Court. This research was conducted to find out the basic philosophy of the transformation in order to have a strong basis/footing in the application of a legal norm, besides that the author proposes a futuristic proposal to change Article 9 of the Anti-Corruption Law into a material offense with the addition of elements of forgery that are detrimental to state finances/the state economy.